Reaping mango fruits round-the-year - Misra, A. K.; Selvarajan, M.; Subbiah, A.; Thamaraiselvi, S. P. (Indian Horticulture, 2019)
In India, wide agro-ecological diversity and varietal wealth available across the country can be exploited for extending season of mango availability for better returns to growers. The season for commercial production of mango in India is only for a limited period from April to June, putting it in a disadvantageous position compared to other countries. Hence, it is necessary to extend the availability of mango out of season so as to make the mango orcharding more remunerative. The strategy should focus on generating mango availability both for domestic and export market by exploiting off-season technology of mango production.